Phytoremediation with Schoenoplectus Americanus and Eichhornia Crassipes in Cyanide Effluents - Angelica Grisela Murillo Advincula; Maria Flor Montanez Machco; Maximo Cisneros Tejeira; Fiorella Vanessa Guere Salazar; Zanhy Leonor Valencia Reyes; Elmer Benites-Alfaro; Alex Segundino Armas Blancas (Chemical Engineering Transactions, 2023)
In Peru, the gold mining industries use cyanide in leaching processes, being the main sources of contamination of ecosystems, current techniques with living organisms are being used to absorb and inhibit the effect of contaminants, such as phytoremediation that through green plants are used to remove exposed contaminants from an area, remediating it to its natural state. The objective of the research was to evaluate the phytoremediation capacity of Schoenoplectus americanus and Eichhornia crassipes, on the cyanide concentration in effluents from the Paltarumi gold mine. A laboratory-scale phytoremediation system was implemented as an alternative treatment, it was executed in pots with different treatments, water from a wetland near the sea, plus cyanide effluent. The results showed that the color of the stems, leaves and roots changed to darker colors with necrotic points, it was evidenced that cyanide affected the growth of the plants, highlighting the Schoenoplectus americanus that achieved a greater height. In root length, Eichhornia crassipes had more extensive roots. In the remaining cyanide in the aqueous solution, the Eichhornia crassipes macrophyte had the highest cyanide retention capacity and in relation to absorption, it was the treatment with Schoenoplectus americanus + Eichhornia crassipes that absorbed over the greatest amount of cyanide with 18,673 mg.L-1 equivalent at 84.8 %, followed by Schoenoplectus americanus and Eichhornia crassipes with 80.5 % and 78.3 % respectively. Therefore, the use of phytoremediation plant species for cyanide absorption is a good alternative as it has environmental advantages due to the non-use of chemical products, low cost and easy implementation.